Factorial composition of the Personal Self-Concept Questionnaire (APE) in Mexican university students - Peinado Pérez, Jesús Enrique; Barrón Luján, Juan Cristobal; Blanco Ornelas, José René; Benitez Hernández, Zuliana Paola; Blanco Vega, Humberto (Acta Universitaria, 2019)
The present study aims to investigate whether the psychometric results proposed by Goñi, Madariaga, Axpe & Goñi (2011) for the Personal Self-concept Questionnaire (APE, from its Spanish initials) are replicated. The total sample was 1485 Mexican university students, with an average age of 20.55 years (SD = 1.86). The factorial structure of the questionnaire was analyzed through exploratory and confirmatory factor analysis. The analyses show that a three-factor structure is feasible and appropriate. The structure of three factors (self-realization, autonomy, and emotional adjustment), based on statistical and substantive criteria, has shown adequate adjustment indicators of reliability and validity. However, the obtained model does not match the one proposed by Goñi et al. (2011). Future research should replicate these findings in larger samples.